Quantitative Video Laryngoscopy to Monitor Recovery from Recurrent Laryngeal Nerve Injury in the Rat. (May 2014) - Mor, Niv; Naggar, Isaac; Das, Olipriya; Nakase, Ko; Silverman, Joshua B.; Sundaram, Krishnamurthi; Stewart, Mark; Kollmar, Richard
Recovery from unilateral vocal-fold paralysis is lengthy, unpredictable, and often incomplete, highlighting the need for better treatments of the injured recurrent laryngeal nerve. To be able to monitor recovery of vocal-fold motion in studies with rats, we developed a procedure for quantitative video laryngoscopy. An asymmetry index was defined as a continuous and robust measure of unequal vocal-fold motion and calculated from spectral-density plots of vocal-fold displacements. In a cohort of 8 animals, unilateral vocal-fold paralysis was observed within seconds after clamping of the right recurrent laryngeal nerve and was accompanied by a markedly negative asymmetry index. Over the next month, the asymmetry index gradually returned to zero, concomitant with a visible recovery of vocal-fold motion. Our results suggest that quantitative video laryngoscopy is a sensitive and discriminating method for monitoring recovery from recurrent laryngeal nerve injury and set the stage for testing novel surgical and pharmacological treatments of unilateral vocal-fold paralysis.